An eugenetic algorithm for delay-constrained minimum-cost routing of multipoint connections - Peter Kortis; Vladimir Olej; Karol Blunar (Communications - Scientific letters of the University of Zilina, 2004)
A special kind of genetic algorithm - eugenic algorithm is presented for constructing minimum-cost tree with delay constraints. Telecommunication network is represented by an undirected graph, which uses three independent metrics: cost, delay and capacity. The efficiency of two different bit representations of individuals (adjacent matrix, list of vertices) is compared.